Streamlining the Diagnosis of Atypical Facial Palsies: A 5-year Review of 805 Patients. Issue 2 (9th February 2022) - Cheung, Lok Ka; Kannan, Ruben Y.; Neville, Catriona; Gwynn, Tamsin; Young, Karen; Ching, Rosanna C.; Nduka, Charles
Abstract : Background: Currently, there are no definitive guidelines in the investigation and management of atypical facial palsies (AFPs). Our aim was to determine the etiology of AFPs presenting to a tertiary facial palsy center and to review the current spectrum of diagnostic and management approaches to these conditions. Methods: A retrospective cohort analysis of attendees at the Queen Victoria Hospital multidisciplinary facial palsy clinic over a 5-year period from 2016 to 2020 was conducted. Demographic data were collated from the QVH Research and Governance team. Those presenting with classic Bell's palsy or Ramsay-Hunt syndrome were excluded. Anyone with atypical presentations (including multiple recurrences, focal neurological deficits, polycranial neuropathies, autoimmune conditions, hemifacial spasms, hearing/balance issues, weight loss, segmental facial palsies, and gradual onset presentations) were included under the AFP category. These patients were subjected to standard serological and radiological investigations and their follow-ups were reviewed. Results: A total of 849 patients were identified, and 805 had actual facial palsy presentations. Of these, 172 patients had AFP. The majority of these patients had MRI imaging tests, which were useful, but the remaining serological tests were found to correlate more with symptom clusters and specific questions rather than with random tests for all AFPs. Conclusions: Although serological and radiological investigations help in the diagnosis of AFP, specific questions and presentations help streamline the diagnosis, without affecting its accuracy whilst reducing unnecessary tests and, thereby, cost and time. We present an algorithm organized by specific questions of presentations in those with AFPs.